De novo OAB After ATOMS: An Underestimated Problem or a Rare Side Effect? - Schönburg, Sandra; Bauer, Wilhelm; Mohammed, Nasreldin; Brössner, Clemens; Fornara, Paolo (Frontiers in Surgery, 2019)
Background: The urinary incontinence system ATOMS (A.M.I., Austria) generates suburethral compression through its sphincter cushion. To what extent the ATOMS may lead to overactive bladder (OAB) symptoms or which risk factors for these symptoms exist remain unknown to date. We report on our multicentre evaluation on the prevalence, status, and therapy of OAB after ATOMS. Methods: Between 10/09 and 01/17, a total of 361 patients received an ATOMS device in Vienna and Halle. A prerequisite for surgery was persistent male stress urinary incontinence lasting at least 6 months after the primary intervention, as well as the failure of conservative treatment. Patients with a preoperative untreated anastomotic stricture or detrusor overactivity were excluded. In addition to continence and voiding parameters, patient's age, BMI, comorbidities, and pre-treatment strategies of the underlying disease and urinary incontinence were examined. If de novo OAB was present, urodynamics were used for further clarification. Statistical analysis was performed with GraphPad Prism 7® (GraphPad Software, Inc., La Jolla, USA), p < 0.05 considered significant. Results: OAB presented 18 patients (4.9%). Regarding the degree of urinary incontinence as well as uroflowmetry, residual volume and comorbidities, patients with an OAB showed no differences compared to patients without an OAB (p < 0.05). Only previous radiotherapy or urinary incontinence surgery and urethral stricture interventions resulted in statistically significant differences based on the bivariate analysis (p = 0.030, p = 0.006, p = 0.007). The consecutive postoperative urodynamics revealed a sensory OAB in 17 patients and a low-compliance bladder in a patient with newly diagnosed insulin-dependent type II diabetes mellitus. OAB was treated with a standard dose of antimuscarinic drugs and for the low-compliance bladder with botulinum toxin type A. Conclusion: OAB symptoms can occur after ATOMS implantation, but are rare and have no clear correlation to the incontinence device but rather are due to urinary incontinence-related underlying diseases and previous treatments.